2016
DOI: 10.1002/clc.22512
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of First‐ vs Second‐Generation DES According to DAPT Duration: Results of ARCTIC‐Generation

Abstract: There is an apparent benefit with extension of dual antiplatelet therapy (DAPT) beyond 1 year after implantation of drug-eluting stents (DES). Assessment by a Double Randomization of a Conventional Antiplatelet Strategy vs a Monitoring-Guided Strategy for Drug-Eluting Stent Implantation, and of Treatment Interruption vs Continuation One Year After Stenting (ARCTIC)-Generation assessed whether there is a difference of outcome between first-vs second-generation DES and if there is an interaction with DAPT durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…A previous study (ARTIC-Generation; Clinical Outcome of First- vs. Second-Generation DES According to DAPT Duration) also indicated worse clinical outcomes with first-generation DESs compared to second-generation DESs, a difference that appeared to persist even with prolonged DAPT (6.2% vs. 2.6%; HR, 2.31; 95% CI, 1.31–4.07; p =0.004). 24 In the current study, extended DAPT use led to a significant reduction in MACCE in patients who were treated with first-generation DESs. Based on the results of this study and other studies, extended DAPT could be carefully considered for patients treated with first-generation DESs.…”
Section: Discussionmentioning
confidence: 58%
“…A previous study (ARTIC-Generation; Clinical Outcome of First- vs. Second-Generation DES According to DAPT Duration) also indicated worse clinical outcomes with first-generation DESs compared to second-generation DESs, a difference that appeared to persist even with prolonged DAPT (6.2% vs. 2.6%; HR, 2.31; 95% CI, 1.31–4.07; p =0.004). 24 In the current study, extended DAPT use led to a significant reduction in MACCE in patients who were treated with first-generation DESs. Based on the results of this study and other studies, extended DAPT could be carefully considered for patients treated with first-generation DESs.…”
Section: Discussionmentioning
confidence: 58%
“…The recommendations are based on studies confirming the progress observed with the latest generation of DES and the substantial decrease in stent thrombosis rate (2,5). The recommendations published by the ESC in 2017 which proposed to shorten the duration of DAPT post PCI for CCS to 6 months (3), had no impact on the French practices observed in 2018-2019.…”
Section: Discussionmentioning
confidence: 99%
“…Dual antiplatelet therapy (DAPT) is essential after coronary angioplasty to reduce thrombotic complications (mostly stent thrombosis). Advances in devices and techniques have increased the safety of coronary angioplasty by reducing those complications, with the development of the latest generations of drug eluting stent (DES) in particular (1,2). These technological improvements have allowed a reduction in DAPT duration.…”
Section: Introductionmentioning
confidence: 99%
“…Coronary heart disease (CHD) remains the most significant cause of mortality and a substantial contributor to reduced quality of life worldwide [1,2]. Along with improved stent design, procedural techniques, and effective pharmacological treatments, revascularization therapy has become an essential part of the treatment of CHD [3,4]. Nonetheless, cardiovascular and non-cardiovascular death and other ischemic events driven by atherosclerosis after percutaneous coronary intervention (PCI) remain concerning [5].…”
Section: Introductionmentioning
confidence: 99%